Diversity of Staphylococcus coagulase- positive and negative strains of coalho cheese and detection of enterotoxin encoding genes - Colares de Andrade, ANA PAULA; Teixeira de Figueiredo, Evania Altina; Borges, Maria de Fatima; Arcuri, Edna Froeder (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2019)
Three hundred samples of coalho cheese, from 15 different brands, of which seven were handmade made and eight industrialized, were evaluated in relation to the contamination profile by Staphylococcus coagulase-positive and negative and the occurrence of staphylococcal enterotoxin encoding genes. Two hundred and eight isolates of Staphylococcus sp. were subjected to phenotypic identification and 95 were subjected to genotypic identification through femA gene research and detection of genes (sea, seb, sec, sed, see, seg, seh, sei and sej) encoding enterotoxins, using the polymerase chain reaction technique (PCR). A total of 14 species of Staphylococcus were identified, of which three were coagulase-positive and eleven negative, especially: S. aureus, S. xylosus, S. cohnni spp. cohnii, S. saprophyticus, S. epidermidis, S. hyicus, S. lentus, S. sciuri, S. cohnii spp. urealyticus, S. haemolyticus, S. chromogenes, S. lugdunensis, S. hominis e S. intermedius. In all the samples of handmade coalho cheese handmade there was a prevalence of S. aureus; while in the industrial samples S. xylosus (87.5%) and S. cohnii spp cohnii (50%) were predominant. The presence of the femA gene was detected in 95% (38/40) isolates of positive Staphylococcus coagulase and 16.4% (9/55) of coagulase-negative isolates. Among the enterotoxin encoding genes evaluated, there was prevalence of the seh gene (53.2%) in coagulase-positive strains and of the sec gene (46.8%) in coagulase-negative strains. The results suggest a re-evaluation of the Brazilian microbiological standards in relation to the genus Staphylococcus in foods.